The Role of Youth in the Implementation of Climate Change Policies in Indonesia - Agusniar Rizka Luthfia (International Journal of Social Science and Humanity, 2025)
Climate change represents an urgent global crisis that demands immediate and collaborative action. In Indonesia, youth have emerged as crucial stakeholders in the implementation of climate change policies. This study explores the strategic role of young people in advancing climate action, focusing on their engagement through two major non-governmental organizations: WALHI (Wahana Lingkungan Hidup Indonesia) and Greenpeace Indonesia. Adopting a qualitative library research method, the study examines secondary sources, reports, and publications to assess how these organizations empower and mobilize youth in climate advocacy. The findings highlight that youth are not passive observers but active contributors to climate governance. Through educational campaigns, social media activism, public demonstrations, and grassroots initiatives, young individuals raise environmental awareness, promote sustainable practices, and exert social and political pressure on government institutions. Their participation fosters democratic engagement, enhances policy responsiveness, and encourages the inclusion of long-term environmental perspectives in national and regional development agendas. Furthermore, youth play a critical role in bridging scientific knowledge with community-based practices, often initiating innovative and context-sensitive solutions tailored to local environmental challenges. Their digital literacy and ability to build networks across diverse societal sectors amplify their effectiveness in shaping public discourse and influencing policy outcomes. This study concludes that empowering youth is fundamental to achieving meaningful and lasting climate action. Their involvement strengthens both mitigation and adaptation efforts, positioning them as key agents of change who are not only directly impacted by climate change but also committed to securing a more sustainable and just environmental future for Indonesia.